Individual aesthetic culture in the development of the struggle against the threats of "mass culture" - Muhammadievich, Gaybullaev Otabek (International Journal of Psychosocial Rehabilitation, 2020)
Threats of various kinds occurring in the world are increasingly leading to the formation of negative vices in the moral and spiritual consciousness of man in society. Therefore, every state must inculcate in its citizens the ideological and aesthetic immunity that can withstand various spiritual threats. It is possible to get rid of various stereotypes by forming a high aesthetic culture of the individual in the society. This, in turn, makes a person’s goals for the future richer with a sense of beauty, indicating that in this enlightened world, man is the greatest value and its creator.